ANALYSIS OF THE CAUSES, IMPACTS, AND MITIGATION STRATEGIES FOR TIDAL FLOOD DISASTERS IN DUMAI CITY - Febblina Daryanes; Irda Sayuti; Khusnul Fikri; Deci Ririen (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
Tidal flooding in Dumai City has intensified in recent years, causing damage to settlements, infrastructure, and community livelihoods. However, previous studies predominantly focus on technical modeling and lack updated, field-based assessments of post-2020 conditions, especially regarding the effectiveness of recent mitigation efforts. This study aims to analyze the causes, impacts, and mitigation strategies of tidal flooding in Dumai by filling these research gaps. Using a qualitative approach, including semi-structured interviews with BPBD officers, relevant agencies, and affected residents, as well as field observations, the research reveals that tidal floods were triggered by high rainfall, tidal cycles, and inadequate drainage infrastructure before 2021. The impacts include damage to homes, furniture, vehicles, and public roads, as well as health and economic disruptions. Since the construction of 15 floodgates and water pumps in 2021, supported by mangrove planting and increased community participation, flood duration has drastically decreased from several days to approximately three hours. The study concludes that these strategies are effective but require ongoing maintenance and expansion. It is recommended that the government enhance drainage systems, widen mangrove rehabilitation areas, and accelerate relocation plans for high-risk households to ensure long-term resilience.